Fiscal Condition of Sumatra in Decentralization Era - Haryanto, Joko Tri (Research and Development Agency Ministry of Home Affairs, 2018)
Indonesia has been running a decentralized reform era since 1 January 2001. The goal of decentralization is to accelerate the realization of prosperity through the improvement of public services. Fiscal decentralization then became the main benchmark of the successful creation of indicators of regional autonomy in addressing various problems in the regions, especially inequality and poverty. According to government data, Sumatra recorded a major contributor to national GDP growth while facing poverty, inequality constraints and also the largest mining sector. By using the shared and growth analysis and quadrant method, this research tries to provide policy-making recommendations based on the characteristics of the regions in Sumatra. Based on shared analysis, the biggest region is Bengkalis Regency, Riau Province, Siak Regency, Rokan Hilir Regency, and Musi Banyuasin Regency. For the smallest region, it consists of West Nias Regency, North Nias, Toba Samosir, Gunung Sitoli and South Nias. From the growth analysis, it was found that Mesuji Regency, Southeast Aceh Padang Lawas Utara, Kota Padang Panjang and West Nias Regency have the highest growth in Indonesia. From the quadrant method, 20 regions are in quadrant I, about 54 other areas are in quadrant II, and 35 areas are in quadrant III. The largest part of the regional classification in the region of Sumatra is in quadrant IV. Based on these findings, fiscal policy in the future should be prioritized to develop on regional eradication in quadrant IV in terms of Transfer to Region.